Tilik Wong Lara: Visiting Tradition Among Javanese and Its Dynamic During Covid-19 Pandemic - Nusawakan, Arwyn Weynand; Italilpessy, Dirga Maria; Suwartiningsih, Sri (GLOBAL HEALTH SCIENCE GROUP, 2024)
Tilik wong lara’s tradition has become a social bond that takes place in society so it is continued to exist nowday. However, during the Covid-19 pandemic, social support for Covid-19 patients has been hampered due to isolation and physical distancing. This study aims to identify how tilik is carried out as part of a community support and how this tradition has changed in patients and the state of Covid-19. The method of this study is a qualitative method, carried out in Getasan District, Semarang Regency, Central Java on five participants, which was carried out within September 2021. Data was analyzed using thematic data analysis. The results showed that the tradition was carried out as a means of social support for the sick, now underwent adjustments as an effort to maintain cultural patterns, as well as jogo tonggo as another form of social support from tilik. It can be concluded that the tilik wong lara tradition is still maintained as a social value in society and continues to applied despite modifications during the pandemic.